FIGURE 11. A in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean ... - In, First Published (Zenodo, 2022)
FIGURE 11. A, Randallia laevis (Borradaile, 1916), male holotype (cl 24 mm) (after Rathbun 1937). B, C, Acanthonyx petiverii H. Milne Edwards, 1834, juvenile male, cl 4.5 mm, cw 2.8 mm (MZUSP 40671). Semi diagramatic illustrations of the carapace outline and rigtht fifth pereopod propodus and dactylus, lateral view, respectively. Arrows indicate the first branchial lobe inconspicuously developed and the propodus of P5 without the characteristic compressed, dilatated shape. Scales: 1 mm. ... : Published as part of In, First Published, 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 on page 25, DOI: 10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155 ...